Magpalaya para sa halata a digital awareness campaign celebrating effeminacy among queer men engaged in casual sexual relationships and experiences - Reyes, John Vincent
Casual sexual relationships and experiences (CSREs) provide queer men the space to experience intimacy and community building, allowing for personal exploration of gender and sexual identity. However, as evident in geo-social networking applications (GSNAs) like Grindr, CSREs among queer men are tainted by internalized discrimination.